Using Local Short Stories to Improve Students’ Vocabulary - Sariana Sariana; Syarifuddin Dollah; Ahmad Talib (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
The objective of the research was to find out whether or not the use of local short stories could improve students’ vocabulary. This research involved 25 students in grade IX.B of UPTD SMPN 6 Barru. This sample was taken using the purposive sampling technique because the observation showed that students lack vocabulary achievement and have low motivation to learn English. This pre-experimental study employed a one-group pretest-posttest design; the treatment of this research consisted of four meetings in the class. The data were collected through vocabulary tests before and after giving local short stories as treatment in four meetings. The pretest and posttest results were analyzed using SPSS version 25. It showed a significant improvement after local short stories were applied in the treatment, proving that the students’ experimental post-test mean score of 79.92 was higher than their pretest mean score of 41.84. This indicates that local short stories can improve students’ vocabulary achievement.